Effect of sol-gel encapsulation on lipase structure and function: A small angle neutron scattering study - Rodgers, L E; Holden, P J; Knott, R; Finnie, K S; Bartlett, J R; Foster, L J R (Journal of Sol-Gel Science and Technology, 2005)
The application of small angle neutron scattering (SANS) to the characterisation of sol-gel hosts containing biomolecules offers the opportunity to explore the relationship between gel structure and catalyst. A model system involving the immobilisation of Candida antarctica lipase B (CALB) was investigated. Gels were produced by fluoride-catalysed hydrolysis of fixed ratios of tetramethylorthosilicate (TMOS) and methyltrimethoxysilane (MTMS). Phase separation between the enzyme and the evolving sol-gel matrix was minimised by incorporating glycerol into the sol-gel precursor solution. The potential stabilising effect of the NaF catalyst upon the enzyme was also investigated. Scattering studies were conducted on both immobilised lipase and lipase in free solution. Scattering studies on free enzyme provided evidence of multiple populations of enzyme aggregates and showed that choice of solvent affected the degree of aggregation. Both NaF and glycerol affected neutron scattering indicating changes in lipase conformation. Increasing glycerol concentration increased the degree of aggregation and produced differences in solvent packing on the surface of protein molecules. Initial evidence from SANS data indicated that the presence of the enzyme during gel formation conferred structural changes on the gel matrix. Modelling the effect of sol-gel encapsulation on lipase requires comparison of data from free enzyme to the immobilised form. Removal of the enzyme from the sol-gel structure post gelation is necessary to better characterise the modified matrix. This methodological problem will be the subject of future investigations.